2021
DOI: 10.1055/a-1458-2419
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Editing of Flavins for Catalysis

Abstract: The diverse activity of flavoenzymes in organic transformations has fascinated researchers for a long time. However, when applied outside an enzyme environment, the isolated flavin cofactor only shows largely reduced activity. This highlights the importance of embedding the reactive flavin’s isoalloxazine core in defined surroundings. The latter include crucial non-covalent interactions with amino acid side chains or backbone as well as controlled access to reactants such as molecular oxygen. Nevertheless, mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The general usefulness of reduced flavin catalysts is highlighted by recent reductive catalytic reactions with flavoenzymes and a deazaflavin . We found it remarkable that in organic synthesis molecular flavins are extensively applied for oxidations, for example, using commercially available (−)-riboflavin, but they are not applied for reductions. Therefore, we aimed for finding a strategy to use molecular flavins in the reductive 5- exo -trig cyclization of barbituric acid derivatives, which had previously only been reported with superstoichiometric metal reductants (Figure B). , …”
mentioning
confidence: 99%
“…The general usefulness of reduced flavin catalysts is highlighted by recent reductive catalytic reactions with flavoenzymes and a deazaflavin . We found it remarkable that in organic synthesis molecular flavins are extensively applied for oxidations, for example, using commercially available (−)-riboflavin, but they are not applied for reductions. Therefore, we aimed for finding a strategy to use molecular flavins in the reductive 5- exo -trig cyclization of barbituric acid derivatives, which had previously only been reported with superstoichiometric metal reductants (Figure B). , …”
mentioning
confidence: 99%
“…The unique catalytic properties of 3‐Cl were demonstrated by comparison with neutral deazaflavin 2 b and riboflavin tetraacetate (RFTA), which is a prominent flavin derivative used in photooxidation reactions [17b–d] . As expected, with 2 b and RFTA, the photooxidation of 4 b occurred in good to excellent yield under an oxygen atmosphere.…”
Section: Resultsmentioning
confidence: 76%
“…However, although flavins have been shown to be selective in a few cases, the procedure for oxidizing the benzyl position in the presence of a heteroatom, such as sulfur in sulfides or nitrogen in an amino group, has not been described to date (Scheme 2). [17b,21] Similar to other photocatalysts, the need for oxygen during flavin recovery causes chemoselectivity problems.…”
Section: Resultsmentioning
confidence: 99%
“…Flavins can catalyze a range of reactions [3c,22] . Previous work on the use of a gelling flavin derivative for aerobic hydrogenation of olefins showed that the gel phase provided enhanced catalysis compared to the equivalent non‐gelled catalyst due to the formation of reaction cavities [10b] .…”
Section: Resultsmentioning
confidence: 99%